Office Christmas party - Gordon, Josh, (Director); Speck, Will; Bateman, Jason; Munn, Olivia, 1980-; Miller, T. J., 1981- (Hollywood, California : Paramount, 2017)
When his CEO sister threatens to shut down his branch, a man throws an epic Christmas party in the hopes of impressing a potential client that would save his job.
Originally released as a motion picture in 2016.
Dolby digital 5.1, wide screen 1.85:1.
Jason Bateman, Olivia Munn, T.J. Miller, Jillian Bell, Vanessa Bayer, Courntey B. Vance.
MPAA rating: R.
In English, French, or Spanish with optional English, French, Portuguese, or Spanish subtitles.
Closed-captioned.
Keywords: Office parties -- Drama; Sibling rivalry -- Drama; Christmas films; Fiction films; Video recordings for the hearing impaired; Feature films; Comedy films